1591. Infectious Outcomes of Levofloxacin Prophylaxis in Obese vs. Non-obese Patients with Hematologic Malignancies. (26th November 2018) - Kurtti, Amanda; Fritz, Kelly; Elofson, Kathryn; Benefield, Russell
Abstract: Background: Levofloxacin given at a standard dose of 500 mg daily is recommended for antibacterial prophylaxis in patients receiving myelosuppressive chemotherapy. Obese patients have been shown to exhibit enhanced clearance of levofloxacin and may be at risk for prophylactic failure. Methods: This was a single-center, retrospective cohort study evaluating the infectious outcomes of obese (BMI >30 kg/m 2 ) and non-obese (BMI ≤ 30 kg/m 2 ) adult patients who received standard dose levofloxacin as primary prophylaxis after chemotherapy. Patients were included if they were treated at our institution from June 1, 2014 through May 31, 2017 and had National Comprehensive Cancer Network (NCCN) defined intermediate infection risk. Patients were excluded if they were lost to follow-up, treated at another institution for febrile neutropenia (FN), or had renal impairment (estimated creatinine clearance (CrCL) less than 50 mL/minute). The primary endpoint was incidence of FN as defined by NCCN guidelines. Secondary endpoints included 30-day mortality and the correlation between estimated levofloxacin AUC and rates of FN. Levofloxacin AUC was estimated from CrCL using the method of Pai et al. Results: A total of 98 patients met the inclusion criteria (34 obese and 64 non-obese). Estimated CrCL was similar between obese and non-obese patients (mean 84.5 vs. 81.6 mL/minute, P = 0.61), as was estimated levofloxacin AUC (mean 115.1 mg hour/L vs. 107.8 mg hour/L, P = 0.25). FN occurred in 26 patients: 12 (35.3%) obese and 14 (21.9%) non-obese ( P = 0.16). Bivariate comparisons between patients who did and did not experience FN found no significant associations with the weight-related variables total body weight (mean 84.7 vs. 82.0 kg, P = 0.56), BMI (mean 28.8 vs. 28.0 kg/m 2, P = 0.51), or body surface area (1.99 vs. 1.96 m 2, P = 0.62). Multivariate analysis identified presence of mucositis and diagnosis of multiple myeloma as variables independently associated with FN. No patients died within 30 days of the FN event. Conclusion: There were no significant associations between body weight-related variables and FN in this cohort of patients with similar renal function. Obesity should not be a justification for more aggressive levofloxacin dosing schemes when used for FN prophylaxis. Disclosures: All authors: No reported disclosures.